Buying and selling a veterinary practice. Issue 1 (14th January 2016) - Jenkins, Tim
Abstract : The sale or purchase of a veterinary practice is likely to be one of the largest financial transactions that a vet will make. Whether selling or buying, it helps to be prepared in terms of understanding the process and the logistics involved. Tim Jenkins summarises some of the key considerations.